(untitled) (Current Horticulture, 2024)
The passive underground storage of potato (Solanum tuberosum) was designed and potato tubers of Kufri Jyoti, Kufri Himalini and Kufri Girdhari were stored in passive underground storage during November 2022 - April 2023 at Defense Institute of High-Altitude Research, Leh Ladakh. Of three cultivars, tubers of Kufri Girdhari showed lowest total weight loss as compared to other varieties. Potato is most valued non cereal crop in Ladakh. It is consumed by the locals as well as the army deployed here, all through the season. The crop is multiplied vegetatively using tuber as seed material usually (Paul et.al., 2022). The crop is cultivated in May and harvested in September. During the harsh cold winter, continuous supply of fresh vegetables is not possible as the region remains landlocked during November - May. Transport of vegetables through air route is expensive as it charges around Rs 130/kg. In such cases, storage of potato for long period of winter becomes essential (Singh and Srivastava ,2012). Moreover, to address food insecurity, it is crucial to boost productivity and expand the area dedicated to potato production (Jatav et.al., 2023) The study was carried out in underground passive storage located at Leh (77.57298º E; 34.13298º N; elevation 11482 ft) during November - April (Fig 1). Potato tubers of Kufri Jyoti, Kufri Himalini and Kufri Girdhari were used for study. Potatoes were properly cured, free from damages and stored in perforated leno bags (35kg each). The observation for weight loss and rotting were done monthly. Temperature and humidity were also recorded during the storage period with testo 175 H1 data logger.